Causes for postharvest loss in tomato cultivars commercialized in Ceasa, Ceará, Brazil - Teixeira, Isla Simplicio; Rufino, Maria do Socorro Moura; Pinto, Ciro de Miranda; Almeida, Antônio Odálio Girão de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
The research consisted in identifying the post-harvest losses of tomato cultivars ’Longa Vida’ and ’Cajá’ commercialized in Ceasa-Ceara, identifying the main difficulties of their commercialization. The actions were evaluated in two stages: Interviews with 50 licensees who sell tomatoes; Evaluation of the main losses of tomato on benches and/or boxes. The fruits, before commercialization, were subjected to sampling analysis containing 899.4 kg in the “Initial Quality” sample, to determine the main damages and 191.8 kg in the “Discard” sample, to determine the real loss of the product. Subsequently, the percentage and average of fruits at different stages of maturation (green, horticultural maturity and fully ripe) were calculated, with mechanical and physiological injuries, phytopathological diseases, pest attack and absence of damage. The cultivar Longa Vida is the most commercialized at Ceasa (70%). Transport is carried out in open trucks (80%) and storage is on benches and/or boxes (86%). For tomato marketing, plastic packaging is used (98%), and incorrect handling is the main factor that makes marketing difficult (32%). In the ’Initial Quality’ sampling, 68.99% of the cultivars presented horticultural maturity (47 kg). 18.07% of the most frequent injuries are mechanical (12 kg) and 10.55% to physiological damage (7 kg). Of the total “discard” sampling, about 60.58% (8 kg) of the fruits showed horticultural maturity and 36.43% showed damage due to mechanical injury (48 kg) and 21.90% damage due to pest attack (2.9 kg). Post-harvest losses can be reduced with the implementation and use of refrigerated chambers.